Do Private Equity Fund Managers Earn Their Fees? Compensation, Ownership, and Cash Flow Performance - Robinson, David T.; Sensoy, Berk A. (Review of Financial Studies, 2013)
We study the relations between management contract terms and performance in private equity using new data for 837 funds from 1984–2010. We find no evidence that higher fees or lower managerial ownership are associated with lower net-of-fee performance. Nevertheless, compensation rises and shifts to performance-insensitive components during fundraising booms. Further, the behavior of distributions around contractual fee triggers is consistent with an underlying agency conflict between investors and fund managers. Our evidence suggests that managers with higher fees deliver higher gross performance, and highlights that agency costs are an inevitable consequence of the information frictions endemic to agency relationships.